2003
DOI: 10.1038/sj.ijo.0802327
|View full text |Cite
|
Sign up to set email alerts
|

Associations between a polymorphism in the 11 beta hydroxysteroid dehydrogenase type I gene and body composition

Abstract: We investigated 11 beta hydroxysteriod dehydrogenase type 1 (11bHSD-1) sequence variants in 103 healthy overweight (BMI 42 s.d.) and 160 nonoverweight (BMI -2 to +2 SD) children to examine the associations between body composition and 11bHSD-1 polymorphisms. A total of 4.3% of children were homozygous and 30.0% heterozygous for an adenine insertion in intron 3 (ins4436A). By ANCOVA (adjusting for age, sex, race, and height), BMI-s.d. differed according to ins4436A genotype (Po0.005), with the greatest BMI-SD f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 21 publications
2
33
0
1
Order By: Relevance
“…19 There is also one study that has reported a positive association of the ins4436A SNP in the HSD11B1 gene with body mass index (BMI) and insulin resistance in obese children. 20 Thus, the objective of the current study was to evaluate whether the unstudied variations in the HSD11B1 gene are associated with obesity and features of metabolic syndrome in a cohort of Spanish children.…”
Section: Introductionmentioning
confidence: 99%
“…19 There is also one study that has reported a positive association of the ins4436A SNP in the HSD11B1 gene with body mass index (BMI) and insulin resistance in obese children. 20 Thus, the objective of the current study was to evaluate whether the unstudied variations in the HSD11B1 gene are associated with obesity and features of metabolic syndrome in a cohort of Spanish children.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that 11␤HSD1 activity and expression in subcutaneous adipose tissue (SCAT) are positively correlated with obesity and insulin resistance in both men and women (11)(12)(13)(14)(15)(16)(17). In addition, polymorphic variability at the 11␤HSD1 locus is associated with increased waist-to-hip ratio in adults (18) and with body composition and insulin resistance in children (19).…”
mentioning
confidence: 99%
“…Increased concentrations of 11␤-hydroxysteroid dehydrogenase type 1 (11␤-HSD-1), the enzyme that catalyzes the local reactivation of circulating inert cortisone (11-dehydrocortisosterone in rodents) to cortisol (corticosterone) have been found in adipose tissue of obese patients (3)(4)(5)(6) and are closely related to adipose tissue accumulation and features of insulin resistance (5,6). Polymorphic variability at the 11␤-HSD-1 locus is associated with greater BMI, waist circumference, waistto-hip ratio, and insulin resistance in children (7) and with increased waist-to-hip ratio in adults (8). Transgenic mice with adipocyte-targeted 11␤-HSD-1 overexpression developed a visceral obesity that was exaggerated by a high-fat diet (9).…”
mentioning
confidence: 99%